Professional Development for Novice EFL Lecturers: Policy and Practices at University of Muhammadiyah Malang - Sumarsono, Puji (Proceeding of International Conference on Teacher Training and Education, 2016)
Higher education institutions tend to recruit experienced lecturers instead of novice lecturers because experienced lecturers guarantee the quality of teaching and learning process as well as effective management since it does not take time, more money, and special programs to make them qualified. In contrast, Language Center (LC) of UMM prefer recruit novice lecturers. This paper, therefore, aims to explore the policy, practices as well as the challenges of professional development for novice English as a Foreign Language (EFL) lecturers. In-depth interview and document analysis were applied to investigate the problems. It was found that the policies of LC are to be the center for professional development which should recruit novice lecturers and most of the lecturers are alumni of English department of UMM. The practices for the professional development are in form of workshop on teaching and learning English especially ESP, workshop on writing ESP book, workshop on writing articles, induction program, religious speech. Meanwhile, the challenges that the institution face to run this program are divided into internal and external challenges.